# The Rule Of Plato

### By: Abigail van Haastrecht December 4, 2014

## Intro

## Rule Of Plato

1) 4 + 4 squared/ 4-1 (3) = 4 squared/ 4+1 (5)

2) 6 + 6 squared/ 4 -1 (8) = 6 squared/4+1 (10)

3) 8 + 8 squared/ 4-1 (15) = 8 squared/ 4+1 (17)

4) 10 + 10 squared/ 4-1 (9) = 10 squared/ 4+1 (11)

5) 12 + 12 squared/ 4-1 (11) = 12 squared/ 4+1 (13)

6) 14 + 14 squared/ 4-1 (13) = 14 squared/ 4+1 (15)

7) 16 + 16 squared/ 4-1 (15) = 16 squared/ 4+1 (17)

8) 18 + 18 squared/ 4-1 (17) = 18 squared/ 4+1 (19)

9) 20 + 20 squared/ 4-1 (19) = 20 squared/ 4+1 (21)

10) 22 + 22 squared/ 4-1 (21) = 22 squared/ 4+1 (23)

## Rule Of Pythagoras

1) 3 + 3 squared/ 2-1 (2) = 3 squared/ 2+1 (4)

2) 5 + 5 squared/ 2-1 (4) = 5 squared/ 2+1 (6)

3) 7 + 7 squared/ 2-1 (6) = 7 squared/ 2+1 (8)

4) 9 + 9 squared/ 2-1 (8) = 9 squared/ 2+1 (10)

5) 11 + 11 squared/ 2-1 (10) = 11 squared/ 2+1 (12)

6) 13 + 13 squared/ 2-1 (12) = 13 squared/ 2+1 (14)

7) 15 + 15 squared/ 2-1 (14) = 15 squared/ 2+1 (16)

8) 17 + 17 squared/ 2-1 (16) = 17 squared/ 2+1 (18)

9) 19 + 19 squared/ 2-1 (18) = 19 squared/ 2+1 (20)

10) 21 + 21 squared/ 2-1 (20) = 21 squared/ 2+1 (22)